Anti-tumor activity of metformin in human epidermal growth factor receptor 2 positive breast cancer cells - Huda, Fathul; Sari Ekawati,; Anindy Putri Addina,; Ahmad Faried,; Berbudi, Afiat; Rusdiana, Taofik; Tenny Putri,; Nurul Qomarilla,; Hilfi, Lukman; Setiawan, Iwan; Bashari, Muhammad Hasan (Penerbit Universiti Kebangsaan Malaysia, 2021)
Breast Cancer (BC) is the leading cause of cancer death in women. One BC subtype is very aggressive with amplification of human epidermal growth factor receptor 2 (HER2) protein. Although specific HER2+ targeting agents are available, most of HER2+ BC patients develop resistant to these agents. Recent studies show that metformin, is able to become anti-tumor in various cancer cells. This research aims to evaluate anti-tumor activities of metformin to HER2+ BC cells in both sensitive and resistant to trastuzumab. A series of assays were performed to evaluate metformin anti-tumor activities in HCC-1954 and SKBR-3 HER2+ BC cells. MTT assay was performed to evaluate cell death, and inhibitory concentration (IC50), while scratch assay was performed to assess inhibition of cell migration and clonogenic assay to assess cell proliferation. p<0.05 was considered to be significant. Metformin could suppress the number of HER2+ BC cells. Viability assay showed suppression of viable cells after metformin incubation of 60 and 600 µM compared to control, 30 and 90%, respectively. Surprisingly, IC50 of metformin was smaller in HER2+ BC HCC-1954 cells that resistant to trastuzumab compare to the sensitive one (SKBR-3). Both were below 1 µM, with R2 more than 0.95. Additionally, clonogenic assay showed less colony number and colony area with at least p < 0.05 in colony number and p < 0.01 in the area. In addition, metformin inhibited cell migration of HER2+ BC cells. Metformin shows a potency as anti-tumor by inducing cell death, inhibiting cell proliferation and cell migration of HER2+ BC cells.